Sex-differentiated impact of simulated microgravity on cognitive performance and cerebral haemodynamics: Methodological triangulation of EEG, fNIRS and blood pressure during HDBR in a population with an astronaut profile - Cáceres Benítez, Karen Lizbeth (2025)
This study investigates the effects of simulated microgravity, focusing on Head-Down Bed Rest (HDBR) on cognitive performance and cerebral hemodynamics in men and women. Therefore, four men and three women were assessed for memory, delayed recall, attention and executive functions using the Montreal Cognitive Assessment (MoCA) under the experimental conditions. Electroencephalography (EEG) and functional near-infrared spectroscopy (fNIRS) were performed to investigate neuronal and hemodynamic activity, with particular focus on temporal [theta-band (4-8 Hz)] and frontal [beta-band (12-30 Hz)] activity. The results suggest that men’s cognitive abilities deteriorate more, as evidenced by poorer MoCA scores and faster task completion times, which could indicate a less efficient work process. On the other hand, women had longer processing times, which could indicate that they are exposed to greater cognitive challenges under microgravity conditions. The neurophysiological analyses also revealed remarkable differences: men showed greater variability of event-related potentials (ERPs) in the beta band, while women showed more synchronized cortical activity. The fNIRS data indicated that brain activation was more localized in men, while women showed broader cortical involvement. Interestingly, despite these cognitive and neurophysiological differences, blood pressure regulation remained stable in both groups during the HDBR period. These results show that it is necessary to apply certain science-based measures to optimize cognitive abilities and mental health during a trip in real microgravity conditions, with strategies best suited for both men and women.